Business decision-making and complex thinking: A bibliometric study - Ernesto Armando Pacheco-Velázquez; José Carlos Vázquez Parra; Marco Cruz-Sandoval; David Ernesto Salinas-Navarro; Martina Carlos-Arroyo (Administrative Sciences, 2023)
Complex thinking is an important tool for effective decision-making, as it helps people to better understand uncertain situations by considering the multiple variables and relationships involved in a situation, thus being able to identify patterns and connections that would not otherwise be evident. This article presents the results of a bibliometric study to identify academic publications that consider the correlation between decision-making in the business area and complex thinking competency and its sub-competencies. The intention was to have a theoretical horizon that provides a complete overview of the current academic situation regarding the correlation of both professional skills to identify areas of opportunity for new studies. Methodologically, we conducted a literature review using Scopus and Web of Science databases under the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) protocol from which a sample of 339 articles related to both topics was obtained. R, Rstudio, and Bibliometrix were used for the quantitative analysis of the data. The results showed an academic tendency to associate decision-making in business with critical thinking, paying little attention to the other sub-competencies of complex thinking. Furthermore, we found a concentration of research in specific universities and countries, repeating a tendency to study only a few sub-competencies. Overall, this work sheds light on the broad opportunity to link the complex thinking macro-competency with decision-making in business, to provide more extraordinary skills and tools to future professionals.
Keywords: 350; business decision-making; complex thinking; educational innovation; future of education; higher education; professional education